A Compatible Marketing Strategy for the Faculty of Distance Education Institution - Hadianti, Siti; Prakoso, Teguh; Brillianing PRATIWI; Memet CASMAT; Ucu RAHAYU; Siti AISYAH; Fitra JAYA (RADINKA JAYA UTAMA PUBLISHER, 2023)
As a prominent distance education institution, Universitas Terbuka (UT) plays a vital role in enhancing educational equity for Indonesian citizens by offering flexible and cost-effective learning opportunities. However, the exposure of UT, particularly the Faculty of Education and Teacher Training (FKIP), requires further enhancement. The phenomenon that occurs must be addressed by choosing a marketing strategy that targets various groups, particularly millennials. The purpose of this study is to investigate the most compatible marketing strategy for faculty in distance education institutions. In the initial year of this study, two key questions are explored: First, the optimal strategy for UT, specifically FKIP, to market its study program, and second, the most effective approach to diversify and promote UT’s study programs. Employing qualitative research, data was collected from 131 respondents and 80 students across four regional offices, supplemented by insights from marketing experts. The findings reveal the necessity for a balanced approach incorporating both conventional and digital marketing strategies. While the conventional strategy emerged as more effective based on the questionnaire and FGD results, the research highlighted the importance of developing a digital marketing strategy aligned with UT’s identity as a cyber university.